Studio pilota sugli effetti cardiaci e metabolici dell`allenamento di resistenza a moderata altitudine in mezzofondisti - Polizzi, G.; Giaccone, M.; Gervasi, M.; D'Amato, A.; Palma, A.; Bartolucci, C.; Brandoni, G.; Federici, A.; Lucertini, F. (Medicina dello Sport, 2014)
Aim. Moderate-altitude (2000 m) training can increase endurance performance at sea level; it improves physiological parameters, including maximum oxygen uptake, muscle oxygen extraction, red blood cell volume, plasma hemoglobin mass and concentration, and maximal cardiac output and systolic stroke volume; and it can also reduce resting and submaximal exercise intensity heart rate. To date, no studies have investigated the effects of moderate-altitude training on resting cardiac output and systolic blood pressure, and on the metabolic thresholds commonly used in evaluating endurance athletes. The aim of this study was to evaluate blood, cardiac, and metabolic parameters following training and sojourn at moderate altitude (2000 m above sea level). Methods. In this pilot study, 10 middle-distance runners sojourned and trained at moderate altitude for 1 month. Hemoglobin concentration, red blood cell count, mean corpuscular volume, hematocrit, systolic stroke volume, heart rate, and anaerobic threshold were measured before the start of training and at 2 weeks after return to sea level. Results. Comparison of pre- and post-training values showed a significant reduction in resting heart rate and a significant increase in hemoglobin concentration, resting systolic stroke volume, resting cardiac output, running speed at individual lactate threshold and at the blood lactate concentration of 4 mmol/L. Conclusion. Physiological response to moderate-altitude training can predict improvements in sea-level performance. The data from this pilot study will provide the basis for a larger-scale study that will include a control group and additional physiological parameters.